In vitro antimycobacterial activity of six Cameroonian medicinal plants using microplate alamarBlue assay. Issue 4 (December 2015) - Nkenfou, Céline Nguefeu; Mawabo, Isabelle Kamga; Notedji, Augustin; Nkenfou, Jean; Fokou, Patrick Valere Tsouh; Jouda, Jean Bosco; Kuiate, Jules-Roger
Abstract: Objective/background: The latest incidence of tuberculosis (TB) (per 100, 000 people) in Cameroon was 243.00 as of 2011. Over the past 21 years, the value for this indicator has fluctuated between 112.00 in 1990 and 320.00 in 2003. Worldwide, this incidence has also increased, bringing back TB as a reemerging disease. On the same note, resistance to anti-TB drugs has increased, urging the search for new molecules. Methods: This study was carried out to evaluate the antimycobacterial activity of six medicinal plants on the virulent strain, H37Rv, using the microplate alamarBlue assay. Mycobacterium tuberculosis (H37Rv strain) was incubated with decreased concentrations of six plant extracts, ranging from 250 μg/mL to 31.25 μg/mL. After 7 days of incubation at 37 °C, the effects of these plant extracts on the viability of the mycobacteria were evaluated. For each plant extract, the minimal inhibitory concentration was determined. Results: The results showed that the compounds MBC1, MBC24, MBC68, MBC81, MBC117, and MBC118 were the best candidates with minimal inhibitory concentrations of 31.25, 62.5, 125, 62.5, and 125 μg/mL, respectively. Conclusion: These results confirm and validate the traditional use of these plants to treat respiratory diseases, which could be good sources and alternatives of plant metabolites for anti-TB-drug development.